Analysis of typical behavior patterns in groups of winterers as basis for prognostication of their future team-work effectiveness - N. N. Pryvalova; V. I. Sukhorukov (Ukrainian Antarctic Journal, 2005)
This research was focused on studying of coping strategies of three groups of specialists and on determination of the degree of intragroup adaptation for prognostication of their ability to work in conditions of Antarctic expedition. Evaluation of group behavior patterns was performed using S. Rosenzweig method and standard processing of data obtained. It permitted to conclude that the first group’s functioning would be more successful owing to their ability to become aware of their responsibility for difficulties arisen. They are inclined to broaden a set of patterns of problem-oriented coping as well as to resist circumstances and demonstrate more competence and confidence in various communicative situations and are capable to strengthen their own psychological well-being. Representatives of the other groups are more anxious with following forms of defensive behavior as reactions of destructive aggression in conflict situation, emotional fixation on problem in combination with disability to comprehend it, insufficient self-criticism. These forms of defensive behavior as well as insufficient own activity directed on solving the problems arisen can provoke not only escalation of a conflict but form neurotic and psychosomatic symptoms. Everything named above can hinder effective team-work of specialists of these groups.